If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 12x + -3 Reorder the terms: y = -3 + 12x Solving y = -3 + 12x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -3 + 12x
| y=-1/2(-0.5)-4 | | y=-1/2(0.5)-4 | | p-25=67/8(18-6) | | 3q^2=-27q^4+51q^3-9q^2 | | 3(x/2-1)=5x-3 | | p-18=72/5(18-7) | | s^3+7s^2+25s+39=0 | | p-18=23/3(18-6) | | x+(6/4.3)=y | | 4x^3-12x^2+12x+3=0 | | -6*0-4y=24 | | 9x^2-20x+50=0 | | ln(x)=ln(x+4)-ln(3) | | 35y^3-220y^2-175y=0 | | -6x-4*0=24 | | 20x^3+58x^2+42x=0 | | 36x^2-81= | | -8x+83=-85+16x | | -185-35x=0 | | 9y/11=-9 | | 14+3x=2+5x+5 | | 7x+8x=45-90 | | 6x+3=-45-2x | | 5(3x-2)=35+45 | | 2(h-1)=3(h+1) | | (2x-7/12)+x=(2x+7/2)+3 | | 5x^2+7x+95=0 | | .3333(5x-8)=3 | | y=2x+22/5 | | onethird(5x-8)=3 | | 5y=2x+22 | | -4x+13-2x=3x-11 |